2016
DOI: 10.1021/acs.est.6b04382
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for High Concentrations and Maternal Transfer of Substituted Diphenylamines in European Eels Analyzed by Two-Dimensional Gas Chromatography–Time-of-Flight Mass Spectrometry and Gas Chromatography–Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Chemical pollution is hypothesized to be one of the factors driving the strong decline of the critically endangered European eel population. Specifically, the impact of contaminants on the quality of spawning eels and subsequent embryo survival and development has been discussed as crucial investigation point. However, so far, only very limited information on potential negative effects of contaminants on the reproduction of eels is available. Through the combination of nontargeted ultrahigh-resolution mass spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Such plots help guide the search for homologous fluorinated, brominated, and chlorinated POPs, whose molecular and fragment ions are characterized by an exact mass that is smaller than the nominal mass. This has led to the identification of previously unknown (mixed) halogenated POPs in a wide range of environmental media, including freshwater and marine biota, , air, and dust . Unlike chlorinated and brominated compounds that display characteristic isotope patterns, polyfluorinated compound ions are more difficult to recognize because 19 F exists as a single stable isotope.…”
Section: Introductionmentioning
confidence: 99%
“…Such plots help guide the search for homologous fluorinated, brominated, and chlorinated POPs, whose molecular and fragment ions are characterized by an exact mass that is smaller than the nominal mass. This has led to the identification of previously unknown (mixed) halogenated POPs in a wide range of environmental media, including freshwater and marine biota, , air, and dust . Unlike chlorinated and brominated compounds that display characteristic isotope patterns, polyfluorinated compound ions are more difficult to recognize because 19 F exists as a single stable isotope.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic antioxidants are an enormous family of anthropogenic chemicals, and many commonly used antioxidants are complex mixtures of different substances. For example, the antioxidant BNTI (CAS number 184378-08-3) is the benzenamine and N -phenyl reaction products with 2,4,4-trimethylpentene and isobutylene, while another antioxidant (BNST, CAS number 68921-45-9) is the benzenamine and N -phenyl reaction products with styrene and 2,4,4-trimethylpentene. , These antioxidants are technical mixtures that, at minimum, contain monobutyl-, dibutyl-, monooctyl-, dioctyl-, dioctyl-monostyrenated, and monooctyl-monostyrenated substitutes on the benzene ring of DPA. Moreover, the structures of many antioxidants utilized on the global chemical market are largely unknown; manufacturers often keep such information confidential.…”
Section: Knowledge Gaps Of Synthetic Antioxidants and The Pathways Fo...mentioning
confidence: 99%
“…A nontarget study also revealed that Ar-SAs were the main group of contaminants detected in the muscle, gonads, and eggs of European eel ( Anguilla anguilla ), with concentrations in the order of μg/g (wet weight, ww). 29 …”
Section: Introductionmentioning
confidence: 99%
“…A nontarget study also revealed that Ar-SAs were the main group of contaminants detected in the muscle, gonads, and eggs of European eel (Anguilla anguilla), with concentrations in the order of μg/g (wet weight, ww). 29 The ecological risks of these contaminants are not certain, but there is some evidence showing their adverse effects on organisms. As summarized in the literature, 4,30 benzophenonetype UVFs may lead to endocrine-disrupting effects in vitro and in vivo (e.g., rats and fish), while SPAs and their transformation products may be related to hepatic toxicity, endocrinedisrupting effects (e.g., in fish), and carcinogenicity (e.g., in mice).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation